Indian Judiciary on Domestic Violence: Decoding Recent Trend - Yadav, Maneesh; Sahil, Gurudev; Yadav, Pratistha; Goel, Ayush (Jurnal Cita Hukum, 2023)
The stark malignancy of domestic violence which is also referred as intimate partner violence on the state of women hood can be determined by the prevalence of it in the present society. It bears to push women to the brink and fringes of deemed societal ladders.  The brunt of domestic violence lead to exploitation of women be it in the form of physical or be it mental and occurs chiefly in their matrimonial homes. The detrimental effect of this abuse and exploitation regrettably imprints itself not only on the suffering females but to the entire family including children which in turn causes monetary, health and societal issue and concerns.  What separates domestic violence from other crimes and abuses is that in Domestic violence there is familial interrelatedness and hence the victim is a known of the complainant. In contrast to the modern trends of raising the bar of rights for women the domestic violence is considered as a major road block and its waning as precursor for the society to bring female rights at par. However, on the other spectrum an alarming fact has been observed by the judiciary about the registration of sham cases against the husband or his family members or both for the purposes of harassment or extorting money. To carry off the said object the complaints are registered by overstating the facts, by addition of conjectures, overplaying the financial conditions of the husband or his family and misrepresenting relevant facts and materials. The supreme court opined in Rajesh Sharma v. State of U.P. that the bulk of the cases are filed impetuously and over trifling matters.   To comprehend the say of Indian judiciary on instances of false domestic violence and sham complaints registered by the complainant, secondary data-based research is conducted. Landmark Judgement from the apex court and different High Courts are also analyzed. Endeavor has been made to appreciate the liabilities and legal rights of both the parties in the cases of intimate partner violence which is perpetrated towards one another.